2013
DOI: 10.1111/bjso.12035
|View full text |Cite
|
Sign up to set email alerts
|

Relative group size and minority school success: The role of intergroup friendship and discrimination experiences

Abstract: Article (Unspecified) http://sro.sussex.ac.uk Baysu, Gülseli, Phalet, Karen and Brown, Rupert (2013) Relative group size and minority school success: the role of intergroup friendship and discrimination experiences. British Journal of Social Psychology, 53 (2). pp. This version is available from Sussex Research Online: http://sro.sussex.ac.uk/52953/ This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 87 publications
(95 reference statements)
3
48
0
6
Order By: Relevance
“…This can further reduce their mainstream orientation and lead to a decrease in school belonging and engagement, eventually resulting in lower levels of achievement (Wong, Eccles, & Sameroff, 2003). Friendships with mainstream peers were found to mediate the relationship between a lower proportion of immigrants in class and better academic outcomes and buffered the negative effects of perceived discrimination (Baysu, Phalet, & Brown, 2014).…”
Section: School-related Conditions For Acculturation and Adjustmentmentioning
confidence: 98%
“…This can further reduce their mainstream orientation and lead to a decrease in school belonging and engagement, eventually resulting in lower levels of achievement (Wong, Eccles, & Sameroff, 2003). Friendships with mainstream peers were found to mediate the relationship between a lower proportion of immigrants in class and better academic outcomes and buffered the negative effects of perceived discrimination (Baysu, Phalet, & Brown, 2014).…”
Section: School-related Conditions For Acculturation and Adjustmentmentioning
confidence: 98%
“…However, as argued earlier, these schools also provide opportunities for positive contact experiences. A study in four Austrian and Belgian cities showed that ethnic minority students who attended less segregated schools reported more school satisfaction and higher school performance (Baysu et al, 2013). These effects were (partly) explained by students' friendships with ethnic majority peers in their school and existed despite their having experiences with ethnic victimization.…”
Section: Interethnic Relations and Academic Adjustmentmentioning
confidence: 99%
“…However, acceptance of interculturality in the classroom is a problem that arises and affects immigrant students who are discriminated because of their origin and their appearance, which stigmatizes their future personal and professional development (Baysu et al, 2013). Gradual general awareness of the importance of human rights and repercussion in communications media of aggression in schools demand that the parties involved in education intervene in both prevention and treatment of bullying when it occurs.…”
Section: Discussionmentioning
confidence: 99%